The Irrelevant Sound Effect on Serial Recall Is Independent of Age and Inhibitory Control. Issue 1 (3rd April 2022) - Meinhardt-Injac, Bozana; Imhof, Margarete; Wetzel, Nicole; Klatte, Maria; Schlittmeier, Sabine J.
ABSTRACT: The Irrelevant Sound Effect (ISE) refers to the disruptive effects of irrelevant and to-be-ignored sounds on cognitive performance. It is an empirical phenomenon of great practical relevance in environments in which cognitive performance has to be achieved in the presence of task-irrelevant background sounds, e.g., in classrooms and study environments. The present study aims to test for developmental differences in susceptibility to classroom noise while taking individual inhibitory control into account. To this end, younger children (8–10 years, n 1 = 57), older children (11–12 years; n 2 = 73) and adults (19–32 years; n 3 = 52) worked on a serial recall task and a paired-associative recall task during classroom noise as irrelevant changing-state sound and during silence. We found that the serial recall performance was similarly impaired by classroom noise in all three age-groups. In contrast, disruption by classroom noise was not evident in paired-associative recall in any age group. Individual susceptibility to the detrimental noise impact was neither associated with age nor with inhibitory control as measured by means of the Stroop task. Theoretical implications of the findings for explaining developmental differences in the ISE by interference- or attention-based mechanisms are discussed.